2017
DOI: 10.1515/nsm-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Metal hydrogen sulfide superconducting temperature

Abstract: Éliashberg theory is generalized to the electronphonon (EP) systems with the not constant density of electronic states. The phonon contribution to the anomalous electron Green's function (GF) is considered. The generalized Éliashberg equations with the variable density of electronic states are resolved for the hydrogen sulphide SH 3 phase under pressure. The dependence of both the real and the imaginary part of the order parameter on the frequency in the SH 3 phase is obtained. The Tc = 177 K value in the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Currently available theoretical results for T C of H 3 S from the phononic theories mentioned in section 1 are represented in figure 1 by various gray symbols [2,4,8,10,11,13,14,[16][17][18]; the legend indicates the crystal structure where given. In addition to its dependence on pressure and structure, calculated T C is seen to vary anneal, green circles with center dot, and < RT anneal, blue circles (from [1,5,6]).…”
Section: T C Of H 3 Smentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available theoretical results for T C of H 3 S from the phononic theories mentioned in section 1 are represented in figure 1 by various gray symbols [2,4,8,10,11,13,14,[16][17][18]; the legend indicates the crystal structure where given. In addition to its dependence on pressure and structure, calculated T C is seen to vary anneal, green circles with center dot, and < RT anneal, blue circles (from [1,5,6]).…”
Section: T C Of H 3 Smentioning
confidence: 99%
“…Temperature dependence of critical fields H CF and associated magnetization extrema M CF are shown in figure 2, Variation of measured T C of H 3 S with applied pressure P for ⩾RT (room temperature) anneal, green circles with center dot, and <RT anneal, blue circles (from [1,5,6]). Gray symbols are various theoretical calculations denoted as (D) [2], (E) [4], (P) [8], (A) [10], (K) [11], (G) [13], (F) [14], (S) [16], (К) [17], and (J) [18]; structure indicated where available. Red square symbol (H) corresponds to T C0 from this work.…”
Section: T C Of H 3 Smentioning
confidence: 99%
“…e Eliashberg equations are strong-coupling extensions to the original BCS theory. Calculations with this theory can be found where they study the high T c in sulfur hydride as a result of the variability in the DOS within the band [30]. Many theoretical calculations based on Eliashberg theory for H 3 S can be found in the literature and also in [31], where the authors also provide an optical spectroscopy study for this material and found spectroscopic evidence that the superconducting mechanism in H 3 S is due to the electron-phonon interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The Eliashberg equations are extensions for strong coupling of the original BCS theory. Calculations with this theory can be found where they study the high-T c in sulfur hydride as a result of the variability in the density of states in the band [25]. Many theoretical calculations based on Eliashberg theory for H 3 S, can be found in the literature among them in [26], where the authors also provide an optical spectroscopy study for this material and found spectroscopy evidence that the superconducting mechanism in H 3 S is the electron-phonon interaction.…”
Section: Introductionmentioning
confidence: 99%